Solubility‐Limited Small Molecule for Stable High‐Capacity Potassium Storage - Wu, Lei‐Feng; Xiao, Ji‐Miao; Luan, Cui‐Zhou; Xie, Mo; Li, Yu‐Yang; Bin, De‐Shan; Zuo, Jing‐Lin (Small (Weinheim an der Bergstrasse, Germany), 2025)
Small molecule electrode materials with superb redox activity have significant applied implications for K‐ion storage, but they face significant challenges like high solubility in electrolytes and low conductivity, limiting their capacity, rate, and cycling stability. Herein, a series of Ni‐bis(dithiolene) (NiS4)‐based small molecules are designed with control of various redox‐active substitutional groups for K‐ion batteries anode materials. It is identified that bis[1,2‐di(pyridine‐4‐yl) ethylene‐1,2‐dithiolate] nickel Ni[C2S2Py2]2 demonstrates a high reversible specific capacity (399 mAh g−1 at 0.03 A g−1) with an impressive rate capability and an exceptional cycling stability (over 99% capacity retention after 1600 cycles). Its extraordinary performance is attributed to the synergy between the NiS4 unit and pyridine group, providing abundant K⁺ storage sites, impressive conductivity, and low solubility. The comprehensive characterizations and theoretical simulation confirm the multistep K⁺ storage mechanism in Ni[C2S2Py2]2, enabling fast charge transfer and excellent rate performance. This work offers new perspectives in building solubility‐limited and conductive small molecule electrode materials with high redox activity for non‐aqueous rechargeable batteries. A series of Nickel‐bis(dithiolene) (NiS4)‐based small molecules with various redox‐active substitutional groups are designed, synthesized, and applied for K‐ion batteries anode materials. The bis[1,2‐di(pyridine‐4‐yl) ethylene‐1,2‐dithiolate] nickel (Ni[C2S2Py2]2) offers high‐density K‐ion storage sites and low electrolyte solubility, resulting in high reversible capacity, impressive rate capability, and exceptional cycling stability.